Perhitungan Kebutuhan Proses Penyemenan pada Casing 4 ½ inch Sumur “A” Lapangan “N” - Amelia Novianti; Pinandita, Aulia Huda; Rasyid, Aly (Jurnal Bhara Petro Energi, 2024)
Seeding is a process of mixing cement powder, water and additives that are then pumped into the well hole through the cover pipe to the annulus along the drilling hole. The success of a drill depends heavily on the success of the drill, so the calculation of the process of drilling is a very important thing to do in the milling industry. Data is obtained through field studies and library studies, then analyzed using casing diagrams and density tables, yields, and additive materials. The research phase included data collection, calculation of slurry volume, additive material calculation, and sack of cement calculation. The results of the research showed that the seeding process required a total volume of 27.55 bbl, with a composition of 98 sacks of grade G cement and 10.52 bbl of water. Additives used with the result included Silica Flour: 32.24 lb, Dispersant Liquid: 6.86 gall, Retarder Liqueid: 2.94 gall, Fluid Loss Control: 98 gall, Bonding Agent: 98 gal, and Defoamer Liquied: 2.94 gall. The equipment used in the sewing process includes the casing shoe, float shoes, casing collars, the float collar, and the shoe track. The research is aimed at ensuring that the seeding process runs smoothly and efficiently, as well as adding knowledge about the calculation of the volume of material required in casing seeding.